Microtus agrestis - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
127. Short-tailed Field Vole Microtus agrestis French: Campagnol agreste / German: Erdmaus / Spanish: Topillo agreste Other common names: Field Vole, Short-tailed Vole Taxonomy. Mus agrestis Linnaeus, 1761, Uppsala, Sweden. Microtus agrestis is in the subgenus Agricola. In most phylogenetic reconstructions, it emerged as sister species to subgenus BlanJordimys with M. afghanus, M. bucharensis, and possibly M. juldasch:. Previously included lavernedii and rozianus as subspecies; two deeply divergent phylogenetic lineages now upgrated to species level. Monotypic. Distribution. W, C & N Europe and N Asia, from the British Is and across C & E Europe (including the Carpathian Basin) and Fennoscandia to Siberia as far E as Lena River, S to NE Kazakhstan, N Mongolia, and extreme NW China (Altai and Barluk Mts in Xinjiang). Descriptive notes. Head-body 92-132 mm, tail 30-53 mm; weight 22-72.5 g. Males are, on average, heavier (weight 35-4 g) than females (32-6 g). The Short-tailed Field Vole is of average size and proportions. Head is blunt, ears are short and hardly protruding from pelage, and eyes are small. Tail is ¢.36% of head—body length. There are six plantar pads, and females have four pairs of nipples, two pairs each of pectoral and inguinal. Fur is long, soft, and dense, with protruding long guard hairs. Dorsum is grayish brown, flanks are more buffy, and belly is gray. Back is sporadically washed buff or rusty. Tail is bicolored, well-haired, and tufted. Juveniles are grayer than adults. Various color variants are reported, occasionally piebalds, pale-coated, rarely albinos, and melanistic. Skull is deep and somewhat narrow, without much expansion of zygomatic arches. Braincase is long, bullae are proportionally large, and interorbital crest is low. Upper incisors are pronouncedly opisthodont. M* has distinct postero-lingualtriangle that is invariably isolated from alternation triangle on outer side. Similar additional triangle frequently occurs on M". Habitat. Ungrazed grassland, fallow land, and ...